A structural mechanism of flavonoids in inhibiting serine proteases. Issue 7 (23rd June 2017) - Xue, Guangpu; Gong, Lihu; Yuan, Cai; Xu, Mingming; Wang, Xu; Jiang, Longguang; Huang, Mingdong
Abstract : The crystal structure of quercerin:uPA reveals that catechol serves as the functional group in inhibiting serine proteases. Abstract : Quercetin is a member of the flavonoids and was previously demonstrated to inhibit trypsin-like serine proteases at micromolar potencies. Different molecular models were proposed to explain such inhibition. However, controversies remain on the molecular details of inhibition. Here, we report the X-ray crystal structure of quercetin in a complex with the urokinase-type plasminogen activator (uPA), an archetypical serine protease. The structure showed that quercetin binds to the specific substrate binding pocket (S1 pocket) of uPA mainly through its two neighboring phenolic hydroxyl groups. Our study thus provides unambiguous evidence to support quercetin binding to serine proteases and defines the molecular basis of the interaction. Our results further establish that natural products with two adjacent phenolic hydroxyl groups (or catechol) are likely to inhibit other trypsin-like serine proteases, a new mechanism formerly under-recognized.